Strengthening our Women's Health Activities on the Basis of Sports Activities - С.Т.Неъматов (Zien Journals, 2022)
The article discusses the unique role of physical education in human health, especially women's health, as well as activities carried out with it.
Keywords: Physical hardening; health improvement; intellectual; individual